Inibidores da Recaptação de Serotonina e Noradrenalina e o risco de quedas em idosos: uma revisão de literatura - Gambarra, Bruna Furtado (2022)
TheSerotonin and Noradrenaline Reuptake Inhibitors are commonly prescribed medications for the treatment of depression in the elderly,. Its relationship withanincreased risk of falls is a constant concern for the health authorities due to the rise of the number of hospitalizations and deaths amongthe geriatric population. The aim of the present study was to describe the relationship between Serotonin and Noradrenaline Reuptake Inhibitors and falls in the elderly. Therefore, a descriptive literature review was carried out, from January to April 2022, with articles collected in the PubMed and MEDLINE® databases, in English and Portugueselanguages. A total of six scientific articles were collected through adaptations of the PRISMA protocol. Most studies have shownthat there was an increase of 30 % in the risk of fallsamong elderliesusing Selective Serotonin Reuptake Inhibitors or Serotonin and Noradrenaline Reuptake Inhibitors when compared to thosenot using these medications. In addition,is important to recognize the elderly who are at greater risk in order to prevent these events. Elderly people with advanced age, especially those aged 75 years or older, female and with illnesses such as depression, diabetes, non-rheumatoid arthritis and coronary heart disease were considered at greater risk of falls. The adequate treatment of depression in the elderly is a challenge for health professionals, as it is necessary to considerate the possible sideeffectsof these drugsand analyze each patient individually.